The NOMAD Experiment at CERN - F. Vannucci (Advances in High Energy Physics)
The purpose of this paper is to review the experimental apparatus and some physics results from the NOMAD (neutrino oscillation magnetic detector) experiment which took data in the CERN wide-band neutrino beam from 1995 to 1998. It collected and reconstructed more than one million charged current (CC) νμ events with an accuracy which was previously obtained only with bubble chambers. The main aim of the experiment was to search for the oscillation νμ into ντ, in a region of mass compatible with the prescriptions of the hot dark matter hypothesis, which predicted a ντ mass in the range of 1–10 eV/c2. This was done by searching for ντ CC interactions, observing the production of the τ lepton through its various decay modes by using kinematical criteria. In parallel, NOMAD also strongly contributed to the study of more conventional processes: quasielastic events, strangeness production and charm dimuon production, single photon production, and coherent neutral pion production. Exotic searches were also investigated. The paper reviews the neutrino beam, the detector setup, the detector performances, the neutrino oscillation results, the strangeness production, the dimuon charm production, and summarizes other pieces of research.